Perceived Influence of Social Media on Multiculturalism in Southern States, Nigeria - Nsude, Ifeyinwa; Osuagwu, Titilayo Remilekun; Etumnu, Emeka Williams (Journal of Sociology: Bulletin of Yerevan University, 2023)
This study investigated the influence of social media on multiculturalism in the southern states of Nigeria. The uncertainty reduction theory served as the theoretical support for the study. The survey research method was employed with a projected population of 17,871,024 in select southern states of Nigeria. The Wimmer and Dominick sample size calculator was used to derive 384 as the sample size. Multistage and purposive sampling techniques were used, and the questionnaire served as an instrument for gathering data while the data was analysed using percentages, charts, and mean analysis. Findings revealed that residents in the southern states use social media for multicultural engagements to a large extent. Findings also show that social media promote cultural inclusion in the southern states of Nigeria by way of enhancing communication competence amongst people from different cultures; it strengthens ties with people from other cultures; and it gives a sense of belonging in a culturally diverse group on social media. It was concluded that social media have a positive influence on multiculturalism in the southern states of Nigeria. It was recommended that residents of the southern states of Nigeria should be encouraged by those stakeholders who are cultural ambassadors to sustain their efforts in using social media for multicultural engagements. Users of social media should be on alert in order to guard against anyone that is capable of causing disunity or tribal war on the social media space. Such a person(s) should be reported so that appropriate action can be taken against them.
Keywords: Social media; multiculturalism; multicultural; culture; groups; southern states